The Effect of Using Electronic bankingin the Performance of commercial Banks - mekhoukh, razika (Journal of Research in Finance and Accounting, 2022)
The study aimed to identify the impact of electronic banking on improving the performance of commercial banks by highlighting the importance of modern electronic banking methods and their role in developing the work of the Bank of Agriculture and Rural Development from the perspective of the workers. In order to achieve the study's objective and test its hypotheses, a special questionnaire was developed to collect data from the sample study. The results of the study showed that electronic banking contributes to improving the banking performance of the bank in question, through the positive impact of electronic banking on improving financial performance by increasing profitability, reducing costs, managing liquidity and reducing risks, as well as improving the efficiency of internal operations by reducing effort and speed in completing operations and responding to customer requirements.